Investigation of copper samples with ion-plasma treatment on the high voltage breakdowns - Baturin, V.A.; Karpenko, A.Yu.; Storizhko, V.Е.; Shutko, V.A. (Вопросы атомной науки и техники, 2018)
The paper presents the results of studies of the effect of ion-plasma treatment of copper surfaces on their resistance to high-vacuum breakdowns. It has been experimentally shown that the plasma and ion-beam modification
of the copper surface leads to an increase of the breakdown voltage from 5 to 35%, depending on the modification
method, and reduces the dark current of the anode-cathode. Представлено результати досліджень впливу іонно-плазмової обробки поверхні міді на її стійкість до високо вакуумних пробоїв. Експериментально показано, що плазмова та іонно-променева модифікації поверхні міді призводять до збільшення пробивної напруги від 5 до 35%, в залежності від методу модифікації, та
зменшення темного струму анодного катода. Представлены результаты исследований влияния ионно-плазменной обработки поверхности меди на её
сопротивление сильным вакуумным пробоям. Экспериментально показано, что плазменная и ионно-лучевая
модификации поверхности меди приводят к увеличению пробивного напряжения от 5 до 35%, в зависимости от метода модификации, и уменьшению темного тока анодного катода.